Analisis Pengaruh Sikap, Norma Subjektif, Persepsi Kontrol Perilaku, Religiusitas Terhadap Niat Membeli Kosmetik Halal (Studi Kasus Pada Konsumen Viva Cosmetics) - Indahastari, Junyar; Fitria, Shoimatul (Diponegoro Journal of Islamic Economics and Business, 2024)
The need for cosmetics is not only for women, but men also use it a lot as part of their needs, not for beauty but for skin health care. The awareness of the Muslim community to pay attention to the halal ingredients contained in cosmetics is still low. Cosmetic products do not enter the body, but they can be related to sacred or unclean matters, if they contain haraam ingredients. This study aims to analyze the effect of independent variables, namely attitudes, subjective norms, perceived behavioral control, and religiosity on purchase intentions as dependent variables on Viva Cosmetics. This study used multiple linear regression analysis techniques using the SPSS Statistics 26 program. The population in this study were Viva Cosmetics consumers in Semarang who used the product within 6 months. The sample used was 100 people with a purposive sampling approach and the data collection method in this study was done through a questionnaire. The results of the analysis show that attitudes, subjective norms, perceptions of behavioral control, and religiosity have a positive effect on the intention to buy Viva Cosmetics.